The impact of related party transactions on firm value in Indonesia: moderating role of good corporate governance - Anita Abigail; Christiana Dharmastuti (Cogent Business & Management, 2022)
In its business operation, a firm may transact with related parties. From an agency theory point of view, agents may use the transaction to maximize the firm value or for personal gain. This study aims to analyze the effect of Related Party Transactions on Firm Value with Good Corporate Governance as moderating variable, represented by the oversight by the majority shareholder and the size of the audit committee. The majority shareholders are divided into three groups: the state-owned company, the foreign-owned company, and the local privately owned company. The study was done using a quantitative analysis method on 58 public companies on Indonesia Stock Exchange included in the LQ45 Stock Index between 2016-2020. The data is processed with the moderated multiple regression model. The result shows no significant relationship exists between Related Party Transactions on Firm Value. The Detrimental Related Party Transactions only become significant on Firm Value when moderated by the state majority ownership. Meanwhile, the Beneficial Related Party Transactions only become significant on Firm Value when moderated by the foreign majority ownership. This study recommends that state-owned companies strengthen the application of their good corporate governance and execute related party transactions only when it adds to the firm value. Managers of foreign companies are advised not to rely entirely on related party transactions with shareholders or sister companies.
Keywords: 650; agency theory; firm value; good corporate governance; related party transactions